Role of multi-biomarkers and algorithms for diagnosis of early-stage ovarian cancer - Upadhyaya, Anupama; Singh, Priti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Our reviews intend to provide a comprehensive update for the diagnosis of ovarian cancer using biomarkers (CA125) and ultrasonography algorithm RMI and ROMA and how to improve our approaches to identify and diagnose ovarian cancer in early stage and improve the survival rate This meta-analysis done in the Department of Obstetrics and Gynaecology Swaroop Rani hospital Prayagraj, Uttar Pradesh. Source of literature was all the standard online articles available in last 3years and also the departmental records of the last 1year following criteria CA125, HE4, RMI, ROMA for screening or diagnosis. Our result on the basis of ODDS ratio and confidence interval (CI) of tumour marker like CA125, HE4, RMI, ROMA from different study. Overall estimation and pooled estimation determined by forest plot and our pooled estimation is present between the 0.8 OR to 1.0 OR and 95 % of confidence interval of the result. Our study concludes that RMI has comparatively good OR ratio and pooled effect of forest plot is in favour of RMI 0.8 OR to 1.0 OR and had good opportunity to identify early-stage ovarian cancer. Our study concludes that RMI score has comparatively good OR ratio and it can be used to identify early-stage ovarian cancer which can help in on time intervention and improved outcomes in such patients.